The East Indian : a novel - Charry, Brinda (Scribner, 2023)
"Meet Tony: insatiably curious, deeply compassionate, with a unique perspective on every scene he encounters. Kidnapped and transported to the New World after traveling from the British East India Company's outpost on the Coromandel Coast to the teeming streets of London, young Tony finds himself in Jamestown, Virginia, where he and his fellow indentured servants--boys like himself, men from Africa, a mad woman from London--must work the tobacco plantations. Orphaned and afraid, Tony initially longs for home. But as he adjusts to his new environment, finding companionship and even love, he can envision a life for himself after servitude. Set during the early days of English colonization in Jamestown, before servitude calcified into racialized slavery, The East Indian gives authentic voice to an otherwise unknown historic figure and brings the world he would have encountered to vivid life"--